Analisis Pengaruh Disiplin Absensi Karyawan terhadap Kinerja Operasional Optimum Gym - Auliya, Nisa; Rachmansyah, Arief (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the effect of employee attendance discipline on operational performance at Optimum Gym, a fitness service provider that relies heavily on service continuity and staff availability. The research is motivated by persistent issues of absenteeism and tardiness, which have the potential to disrupt daily operations, complicate scheduling, and reduce service quality experienced by customers. To address this issue, the study adopts a quantitative approach using an explanatory research design. Data were collected through structured questionnaires measured on a five-point Likert scale, supported by documentation in the form of employee attendance records and internal operational performance reports. The study population consisted of all employees working at Optimum Gym, and a saturation sampling technique was employed due to the relatively small number of employees, enabling the inclusion of the entire population as research respondents. Data analysis was conducted through a series of statistical procedures, including validity and reliability tests to ensure data quality, classical assumption tests to confirm the suitability of the regression model, and simple linear regression analysis to examine the relationship between attendance discipline and operational performance. The results indicate that employee attendance discipline has a significant and positive influence on operational performance, suggesting that consistent attendance and punctuality contribute directly to smoother operational processes and improved service delivery. These findings provide practical implications for management in designing effective discipline policies and monitoring systems. Furthermore, this study contributes to the human resource management literature by offering empirical evidence from the fitness service industry.